2021
DOI: 10.1007/s00441-021-03493-w
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk between the Notch, Wnt, and SHH signaling pathways in regulating the proliferation and regeneration of sensory progenitor cells in the mouse cochlea

Abstract: Sensory hair cells (HCs) are highly susceptible to damage by noise, ototoxic drugs, and aging. Although HCs cannot be spontaneously regenerated in adult mammals, previous studies have shown that signaling pathways are involved in HC regeneration in the damaged mouse cochlea. Here, we used a Notch antagonist (DAPT), a Wnt agonist (QS11), and recombinant Sonic hedgehog (SHH) protein to investigate their concerted actions underlying HC regeneration in the mouse cochlea after neomycin-induced damage both in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Given the crosstalk between Wnt and Shh signalling in regulating proliferation in sensory progenitors 70 , understanding their interrelationship with metabolism during this process has significant impact for HC regeneration. Untangling the interactions between components of the Shh, Bmp7 and glycolytic signalling networks will further our understanding of how hair cells might be morphologically specified for auditory coding during their formation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the crosstalk between Wnt and Shh signalling in regulating proliferation in sensory progenitors 70 , understanding their interrelationship with metabolism during this process has significant impact for HC regeneration. Untangling the interactions between components of the Shh, Bmp7 and glycolytic signalling networks will further our understanding of how hair cells might be morphologically specified for auditory coding during their formation.…”
Section: Discussionmentioning
confidence: 99%
“…Here we found a positive interaction of Wnt-Shh signaling in the Notch inhibitory profile. One group comprehensively studied the interaction between Notch-inhibition and Wnt-signaling activation in the regenerative response of mice hair cell progenitors of the inner ear (Li et al, 2015; Wu et al, 2016; Ni et al, 2016; Wu et al, 2021). Moreover, their most recent publication demonstrated the crosstalk between Notch, Wnt, and Shh signaling pathways in the reparative response of the cochlea after cytotoxic neomycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their most recent publication demonstrated the crosstalk between Notch, Wnt, and Shh signaling pathways in the reparative response of the cochlea after cytotoxic neomycin treatment. The study showed that Notch inhibition and SHH-Wnt treatment promoted progenitor proliferation and activation of a regenerative response (Wu et al, 2021). The study evaluated the combinatorial effects of the inhibitor DAPT, the Wnt agonist QS11, and recombinant Sonic Hedgehog (rmShh) in mice cochlea and their potential regenerative response after neomycin treatment.…”
Section: Crosstalk Between Notch Inhibition and Wnt-shh Signaling In ...mentioning
confidence: 99%
“…Several studies using neonatal mammalian cochlear explants have shown that inhibition of Notch signaling by pharmacologic agents or gene therapy results in hair cell regeneration from supporting cells [17,150,[167][168][169][170][171]. Bai et al showed that in undamaged neonatal cochlear explants, inhibition of Notch generated increased OHC numbers.…”
Section: Manipulating a Single Signaling Pathwaymentioning
confidence: 99%